<span>Lets make it clear: You would have a positive answer when the value you are looking for has to be a positive number. On the other hand you would have a positive and a negative answer when you take the square root of something that doesn't have to be positive. it could be either because when a negative number is squared it becomes positive and when a positive number is squared it stays positive as well.</span>
Sorry I am a little late...
a = -2
b = -9
Here is how to solve the problem.
First thing I did was multiply the first equation by -2 so that we can eliminate the the b. After you multiply it by -2, your new equation is -16a + 8b = -40.
You leave the second equation alone and all you do is combine like terms. So -16a+5a is -11. And you eliminate the b. Then you're going to do -40+62 which is 22. So it's -11a=22 and then you have to solve for a. What I did was I multiplied the whole thing by minus to turn the a positive. So then it's 11a=-22. Pretty easy, the final step is to simplify. -22/11 is -2. ;D
So there you have your first answer.
a = -2
Now we're going to use the first answer to help us find b.
For the second equation, all you're going to do is plug in that a.
5 (-2)-8b=62
-10 - 8b = 62
Now we move the -10 to the other side...
-8b = 62 + 10
-8b = 72
Multiply the whole thing by negative once again to turn the b positive.
Now we have 8b = -72
The final step is to simplify. -72/11 = -9
b = -9
Hope this makes sense! Also I had the same question on my test and I got it right. :)
Answer is B.
8^1/3 = (2^3)^1/3 = 2
Anwser would be 18/14 simplified to 9/7